Pengendalian Penyakit Diplodia Pada Tanaman Jeruk Dengan Bubur California dan Campuran Antara Insektisida, Fungisida & Zat Pengatur Tumbuh - Tiara Anggraini; Salamiah Salamiah; Zairin Zairin (Agroekotek View, 2018)
Citrus plants (Citrus sp.) Currently experiencing major problems with the presence of diplodiadisease both wet and dry. The purpose of this study was to determine the effect of Californiaporridge and mixture of Microthiol, Primavit, Sidametrin and Ridomil against diplodia skindisease in Siam Banjar orange plant in Batola district. This research was conductedexperimentally using Completely Randomized Design. Based on the results obtained bycontrolling diplodia disease with no treatment (control), california slurry, and the mixturebetween pesticides and growth regulators did not have a significant difference. The largestaverage yield reduction was on the california slurry treatment of 3.15 cm2, followed by thesecond largest reduction area by a mixture of pesticides and growth regulators by 2.49 cm2 andthe widest reduction area of attack by no pesticied (control) of 1.39 cm2